The case of atypical anorexia nervosa - Ivanov, Mykola (Psychosomatic Medicine and General Practice, 2018)
Background. Anorexia nervosa is a syndrome characterized by a deliberate and extremely persistent restriction in food, which often leads to cachexia. The leading symptom is the idea fixe about conviction in overweight, distorted perception of the one’s body in which the “fear of obesity” and the attitude to weight loss are formed. Anorexia nervosa, according to ICD-10, relates to eating disorders, which are behavioral syndromes associated with physiological disorders. The complexity of diagnosis and treatment is associated with the tendency of patients to dissimulation, late referral of parents and the low curability of psycho-pathological symptoms, the complexity of rehabilitation issues. Objective. To demonstrate an atypical clinical picture of the anorexia nervosa case. Materials. For the study purpose clinical history and anamnesis according to the mother were examined. Results. A girl was administered medical treatment and out patiently visited psychologist. During the treatment of side effects, there were no complications. After discharge the girl continues to study at school, has good marks and friendly relations with peers. She became calmer in the family. She has been on maintenance therapy for six months. Later medication was discontinued. According to the two-year-old medical history mother does not notice any problems in food behavior. Conclusions. The atypicalness of the clinical picture of anorexia nervosa in this case was manifested in the expressions of the personality accentuation. They manifested themselves in early childhood in heightened suspiciousness, vulnerability, and sensitivity, and were accompanied by various obsessions. In the future, these traits were expressed in psychopathization with a tendency to self-harm and aggressiveness to relatives, and they determined the peculiarities of the clinical picture of anorexia, which led to using an atypical antipsychotic in complex therapy. We mainly associate a good therapeutic effect when staying in the hospital and in the subsequent out-patient treatment with the fact that psychotherapy was conducted almost daily by both a doctor and a clinical psychologist.